2006
DOI: 10.1007/s10995-006-0141-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Programming of Childhood Overweight and Obesity

Abstract: Our review supports prenatal programming of childhood overweight and obesity. MCH research, practice, and policy need to consider the prenatal period a window of opportunity for obesity prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 64 publications
5
97
0
3
Order By: Relevance
“…It has been shown that protein malnutrition during gestation and/or lactation provokes alterations in metabolism when animals or humans reach adulthood. Those observations have supported Barker's or the 'Thrifty phenotype' hypothesis, which postulates that undernutrition during pregnancy imposes metabolic changes in the fetus that will be shifted to a permanent economic metabolism, including in adult life (Hales & Barker 2001); however, if the baby is exposed to a nutritional abundance after birth, the metabolic syndrome is generated, as reported for several experimental models (Vickers et al 2005, Velkoska et al 2008, Bol et al 2009) and epidemiological data from humans who underwent famine early in life (Ravelli et al 1976, Huang et al 2007). This phenomenon is also known as metabolic programming or metabolic imprinting.…”
Section: Introductionmentioning
confidence: 58%
“…It has been shown that protein malnutrition during gestation and/or lactation provokes alterations in metabolism when animals or humans reach adulthood. Those observations have supported Barker's or the 'Thrifty phenotype' hypothesis, which postulates that undernutrition during pregnancy imposes metabolic changes in the fetus that will be shifted to a permanent economic metabolism, including in adult life (Hales & Barker 2001); however, if the baby is exposed to a nutritional abundance after birth, the metabolic syndrome is generated, as reported for several experimental models (Vickers et al 2005, Velkoska et al 2008, Bol et al 2009) and epidemiological data from humans who underwent famine early in life (Ravelli et al 1976, Huang et al 2007). This phenomenon is also known as metabolic programming or metabolic imprinting.…”
Section: Introductionmentioning
confidence: 58%
“…81 However, those authors included only 8 studies of the 14 that we evaluated, primarily those with simultaneous collection of exposure and outcome data and with clinical height and weight measurement, did not calculate a pooled effect size, and did not consider publication bias. This present study overcomes these limitations and allows for an estimation of the public health impact on overweight risk resulting from maternal prenatal smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal overnutrition, evidenced by large infant birth weight for gestational age, is a strong predictor of obesity in childhood and later life (59)(60)(61). A caveat is that, while large infant birth weight for gestational age is generally an indicator of excess fat mass, it may also reflect other growth parameters such that a subset of large infant birth weight for gestational age infants may have increased lean mass (62,63).…”
Section: Prenatal and Postnatal Influencesmentioning
confidence: 99%